Integrasi SERVQUAL, Kaizen, dan Time Study dalam Evaluasi Lean Management untuk Peningkatan Kinerja Layanan Mahasiswa - Puri Sastia Arimbi; Yanti Pasmawati; Septa Hardini; Andries Anwar (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2026)
This study aims to evaluate the implementation of Lean Management in improving service performance at the Student Service Center of Universitas Bina Darma. The service problems include long waiting times, queue congestion, and the absence of clear task distribution among staff, which potentially leads to process waste and reduced service quality. The study employed a descriptive quantitative approach integrating three methods: SERVQUAL to measure student satisfaction (363 respondents), Kaizen to assess employee performance (5 staff members), and time study to analyze process efficiency and waste. Data were analyzed using satisfaction gap calculation, performance indicator assessment, standard time measurement, and classification of value-added and non-value-added activities. The results show that the empathy and assurance dimensions have positive gaps, while responsiveness shows a negative gap indicating low service speed. Standardization and just in time are categorized as high, whereas waste elimination and employee involvement remain low. Although operator capacity is sufficient, the lack of task distribution causes queues and dominant waiting waste as well as non-value-added activities. Therefore, Lean Management improves service performance, but optimization requires workflow restructuring, process digitalization, and increased employee involvement in continuous improvement.